1967
DOI: 10.1159/000458200
|View full text |Cite
|
Sign up to set email alerts
|

Phenolphthalein Monophosphate as a Substrate for the Determination of Alkaline Phosphatase Activity in Tissue Homogenates

Abstract: A simple and accurate method is described for the quantitative determination of alkaline phosphatase in tissue homogenates, utilizing stable buffered phenolphthalein monophosphate as substrate. The compound, which is hydrolyzed at a rate linear to enzyme concentration and incubation time, provides a chromogen directly for spectrophotometric determination. The assay does not require the addition of a non-specific protein or Mg++ for optimal activity and is equally reactive in glass and plastic flasks. The techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1971
1971
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Depending upon the intended use of these rHbs, the presence of this N-terminal methionine residue may not be detrimental. However, for HbS where modifications of the N-terminal valine of either the a-ort8-chains (9,16) have dramatic effects on its oxygen equilibrium and gelation properties, this will present serious problems in the interpretation of any data obtained in mutagenesis studies using such a system. In the present commu- nication, the high yield in N-terminal sequencing of only valine at the N terminus of each mature a-and /3-globin subunit is consistent with the complete removal of the initiator methionine residue by yeast processing enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending upon the intended use of these rHbs, the presence of this N-terminal methionine residue may not be detrimental. However, for HbS where modifications of the N-terminal valine of either the a-ort8-chains (9,16) have dramatic effects on its oxygen equilibrium and gelation properties, this will present serious problems in the interpretation of any data obtained in mutagenesis studies using such a system. In the present commu- nication, the high yield in N-terminal sequencing of only valine at the N terminus of each mature a-and /3-globin subunit is consistent with the complete removal of the initiator methionine residue by yeast processing enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…One approach toward treatment of sickle cell anemia focuses on the HbS molecule itself by reacting it with chemical modifiers that directly alter the functional properties of the protein and indirectly reduce aggregation in vitro (7,8). The number and nature of such susceptible sites has been limited to those hydrophilic side chains with enhanced reactivity because of their location in the protein (8,9). The availability of recombinant DNA technology now permits studies at any site on the HbS tetramer, such as hydrophobic amino acid side chains heretofore not possible to modify by other methods.…”
mentioning
confidence: 99%
“…The polymerization-impairing or -enhancing propensity of mutant hemoglobins, in a binary mixture of mutant hemoglobins and HbS, has facilitated the mapping of several contact residues of the HbS polymer (10 -12). The list of contact sites has been expanded by subsequent studies involving chemical modifications of HbS (13,14) and site-directed mutagenesis (15)(16)(17)(18)(19). However, the identities of all the fiber contacts that are predicted by model studies have not yet been tested in solution experiments.…”
mentioning
confidence: 99%
“…Cerami, Manning, and co-workers showed that cyanate selectively carbamylates amino groups in a positively charged central cavity of hemoglobin, the site to which 2,3-diphosphoglycerate (DPG) binds (16 For personal use only. of hemoglobin's oxygen affinity by modification of this site reduces the tendency of sickle cell hemoglobin to undergo sickling (the condition blocks circulation of the red cells).…”
Section: Methyl Acetyl Phosphatementioning
confidence: 99%
“…The work in Manning's laboratory with Pospischil and Ueno established that methyl acetyle phosphate preferentially acetylates amino groups in the DPG-binding site of human hemoglobin, making it a potentially less toxic alternative to cyanate (16). The reagent is highly selective, reacting mainly with two of the 24 amino groups per alp dimer, the €-amino group of P-lys-82, and the a-amino group of the P-Nterminal valine (3,18).…”
Section: Methyl Acetyl Phosphate and Hemoglobinmentioning
confidence: 99%